Calorie restriction improves metabolic state independently of gut microbiome composition: a randomized dietary intervention trial - Sowah, Solomon A.; Milanese, Alessio; Schübel, Ruth; Wirbel, Jakob; Cevirgen, Ece; Johnson, Theron S.; Hirche, Frank; Grafetstätter, Mirja; Nonnenmacher, Tobias; Kirsten, Romy; López-Nogueroles, Marina; Lahoz, Agustín; et al. (Genome medicine, 2022)
Obesity, Overweight, Weight loss, Gut microbiome, Intermittent calorie restriction